Functional genomics analysis reveals two novel genes required for littorine biosynthesis. Issue 5 (28th November 2019) - Qiu, Fei; Zeng, Junlan; Wang, Jing; Huang, Jian‐Ping; Zhou, Wei; Yang, Chunxian; Lan, Xiaozhong; Chen, Min; Huang, Sheng‐Xiong; Kai, Guoyin; Liao, Zhihua
Summary: Some medicinal plants of the Solanaceae produce pharmaceutical tropane alkaloids (TAs), such as hyoscyamine and scopolamine. Littorine is a key biosynthetic intermediate in the hyoscyamine and scopolamine biosynthetic pathways. However, the mechanism underlying littorine formation from the precursors phenyllactate and tropine is not completely understood. Here, we report the elucidation of littorine biosynthesis through a functional genomics approach and functional identification of two novel biosynthesis genes that encode phenyllactate UDP‐glycosyltransferase (UGT1) and littorine synthase (LS). UGT1 and LS are highly and specifically expressed in Atropa belladonna secondary roots. Suppression of either UGT1 or LS disrupted the biosynthesis of littorine and its TA derivatives (hyoscyamine and scopolamine). Purified His‐tagged UGT1 catalysed phenyllactate glycosylation to form phenyllactylglucose. UGT1 and LS co‐expression in tobacco leaves led to littorine synthesis if tropine and phenyllactate were added. This identification of UGT1 and LS provides the missing link in littorine biosynthesis. The results pave the way for producing hyoscyamine and scopolamine for medical use by metabolic engineering or synthetic biology.